Analisis Faktor-Faktor yang Mempengaruhi Keputusan Konsumen Dalam Berbelanja Pada Ritel Modern dan Tradisional - Saleh, M; Rasyidin, M; Rizal, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Research on the Impact of Product Completeness, Product Variety, Product Quality, and Environmental Conditions on Consumer Purchasing Decisions. This study aims to analyze the influence of shopping comfort and ease of access, product availability, promotions and discounts, technology and innovation, branding, and retail reputation on consumer purchasing decisions. The research was conducted in Bireuen Regency, Aceh Province, Indonesia. The type of research used is explanatory research with a quantitative approach. The data types used in this study are both qualitative and quantitative data. The analysis method employed is the logistic model (LOGIT) to determine the impact on consumer decision-making. The research findings show that the variables of product completeness, more products being better, product quality, and environmental conditions have a significant influence on consumer purchasing decisions in modern retail stores. However, these factors did not have an impact on consumer decisions when shopping at traditional retail stores in Bireuen Regency, Aceh Province, Indonesia.